2018
DOI: 10.1016/j.amsu.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns and outcomes in late middle age (55–65): The intersecting comorbidity with high-risk activity – A retrospective cohort study

Abstract: BackgroundLate middle age (LMA), is a watershed between youth and old age, with unique physical and social changes and declines in vitality, but a desire to remain active despite increasing comorbidity. While post-injury outcomes in the elderly are well studied, little is known regarding LMA patients. We analyzed the injured LMA population admitted to a rural, regional Level 1 Trauma Center relative to outcomes for both younger and older patients.Materials and methodsOur registry was queried retrospectively fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The rate of hypertension also increased from 12% in those younger than 55 years to 53.6% in the 55 to 76 years age group. These two findings are similar to a study conducted by Gale et al,24 who compared the outcomes of late middle age trauma patients relative to younger and older patients. Gale et al24 found the rate of diabetes to be 5.2% in those younger than 55 years, which increased to a rate of 20.3% in trauma patients aged 55 to 65 years, and the rate of hypertension increased from 13.0% in patients younger than 55 years to 41.8% in the 55 to 65 years age category.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The rate of hypertension also increased from 12% in those younger than 55 years to 53.6% in the 55 to 76 years age group. These two findings are similar to a study conducted by Gale et al,24 who compared the outcomes of late middle age trauma patients relative to younger and older patients. Gale et al24 found the rate of diabetes to be 5.2% in those younger than 55 years, which increased to a rate of 20.3% in trauma patients aged 55 to 65 years, and the rate of hypertension increased from 13.0% in patients younger than 55 years to 41.8% in the 55 to 65 years age category.…”
supporting
confidence: 90%
“…Previous studies have indicated an increase in comorbidities among those 55 years or older, 23,24 which may provide further insight regarding the mechanism behind the increase in mortality of those at this consequential age. Compared with those under the age of 55 years, this study also determined a statistically and clinically significant increase in the mean number of comorbidities, with the rate of comorbidities doubling in trauma patients older than 55 years.…”
Section: Discussionmentioning
confidence: 91%
“…Falls were the dominating trauma mechanism (55%) with a marked increase from age group 50 years in line with recent studies (Steyerberg et al 2019 ). The late middle-aged (50–70 years) have recently been identified as a risk group, as they intersect with increasing comorbidity on one hand and keeping up physical and social activity on the other (Gale et al 2018 ; Peeters et al 2019 ). Thus, fall-preventing strategies ought to include this age-group as well.…”
Section: Discussionmentioning
confidence: 99%
“…The EMR-ISS is a validated tool/method to measure injury severity using the International Statistical Classification of Diseases and Related Health Problems 10th Revision, Clinical Modification (ICD-10-CM) [18]. The EMR-ISS score is classified into the following four levels of injury severity: Mild (1-9), moderate (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), severe (25-74), and critical (≥75 or death). For the logistic regression analysis, we divided the EMR-ISS score into two groups: mild and moderate (≤25) versus severe and critical (≥25).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, patients aged over 18 years were included in the study. Specifically, patients were divided into the following four groups by age: Group 1, 18-34 years; Group 2, 35-49 years; Group 3, 50-64 years; and Group 4, ≥65 years [16,23,24].…”
Section: Study Design and Data Collectionmentioning
confidence: 99%